2010
DOI: 10.1016/j.jcrs.2010.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraocular lens power prediction methods using the American Society of Cataract and Refractive Surgeons Post-Keratorefractive Intraocular Lens Power Calculator

Abstract: Methods using surgically induced change in refraction and methods using no previous data gave better results than methods using pre-LASIK/PRK K values and surgically induced change in refraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
109
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 16 publications
3
109
2
1
Order By: Relevance
“…One is the erroneous estimation of corneal power due to altered corneal geometry. [1][2][3][4] The other source is the inaccurate prediction of IOL position (effective lens position [ELP]) by using the corneal radius after refractive surgery. The latter can be avoided by using the Aramberri double-K modification of theoretical formulas or the Haigis formula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the erroneous estimation of corneal power due to altered corneal geometry. [1][2][3][4] The other source is the inaccurate prediction of IOL position (effective lens position [ELP]) by using the corneal radius after refractive surgery. The latter can be avoided by using the Aramberri double-K modification of theoretical formulas or the Haigis formula.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The proposed solution to this error is to evaluate the corneal refractive surfaces separately 5 using devices that can measure both corneal surfaces. These devices include a rotating Scheimpflug camera (Pentacam, Oculus, Inc.), 6,7 a dual Scheimpflug analyzer (Galilei, Ziemer Ophthalmics AG), 8,9 a vertical slitlight scanning device (Orbscan, Bausch & Lomb, Inc), 10,11 and optical coherence tomographers.…”
mentioning
confidence: 99%
“…Using this calculator, our study of 72 post-LASIK/PRK eyes that had cataract surgery found that, compared to methods requiring pre-LASIK/PRK Ks and ∆MR, methods using ∆MR or using no prior data had smaller IOL prediction errors, smaller variances, and greater percentage of eyes within 0.5 and 1.0 D of refractive prediction errors [5]. Another excellent resource is a comprehensive spreadsheet developed by Kenneth Hoffer and Giacomo Savini (http://www.eyelab.com/) [4].…”
Section: Department Of Ophthalmology Baylor College Of Medicine Houmentioning
confidence: 99%
“…We do not have the 6-month postoperative K readings and have to assume that they are the same as the current K values. We are also missing standard topographic data, such as the Atlas numerical map (Carl Zeiss Meditec AG) and the Pentacam equivalent K reading for the central 4.5 mm, as described by Holladay et al 1 The remaining methods result in lower IOL powers; the Shammas, Haigis-L, and modified Masket formulas yield 14.61 D, 13.89 D, and 13.48 D, respectively. The ASCRS mean value recommends using an Acrysof SN60WF IOL (Alcon Laboratories, Inc.) with a power of 14.17 D (range 13.02 to 14.92 D).…”
mentioning
confidence: 99%
“…Both Holladay and Haigis believe that the clinical history method (CHM) provides the most reliable estimate; thus, we would aim closer to 14.77 D and choose an Acrysof SN60WF 14.50 D IOL in this case. 1,3 A conservative approach should always err on the side of myopia, and picking the same IOL with a 15.00 D power is also reasonable. Other considerations include a surgeon's individual correction factors.…”
mentioning
confidence: 99%